Problematika Pembelajaran Bahasa Indonesia Pada Kurikulum Merdeka Di SMA Negeri 1 Pamanukan, Kabupaten Subang - Ayo Suaryo; Riska Oktavia Lurina; Heri Isnaini (Universitas Palan, 2023)
This research was conducted to answer the problems that arise in learning Indonesian in the independent curriculum in phase E or class X at SMA Negeri 1 Pamanukan. This research focuses on teacher readiness, school support, supporting factors, and obstacles related to the implementation of the independent curriculum. In addition, this study also tries to identify steps that can be taken to overcome obstacles in the implementation of the independent curriculum. The method used in this research is descriptive method, which aims to provide a systematic description of some of the existing relationships. The data used in this study were written data obtained from recorded interviews with Indonesian language teachers who taught in phase E or class X. The data was then transcribed into written form. The interview samples were taken from Indonesian teacher respondents who taught in phase E or class X. Based on the results of data collection, it was found that the learning process in general had been carried out well. However, there are several facts that show there are deficiencies in the implementation of this curriculum. One of the deficiencies found is that not all teachers have received the necessary training, and many of them admit that they have not been able to apply learning in accordance with the achievements of the Independent Curriculum. In addition, cognitive assessment to measure student learning outcomes has also not been implemented thoroughly.